Identifying priority technical and context-specific issues in improving the conduct, reporting and use of health economic evaluation in low- and middle-income countries - Alia Luz; Benjarin Santatiwongchai; Juntana Pattanaphesaj; Yot Teerawattananon (BMC, 2018)
Abstract Background The use of economic evaluation in healthcare policies and decision-making, which is limited in low- and middle-income countries (LMICs), might be promoted through the improvement of the conduct and reporting of studies. Although the literature indicates that there are many issues affecting the conduct, reporting and use of this evidence, it is unclear which factors should be prioritised in finding solutions. This study aims to identify the top priority issues that impede the conduct, reporting and use of economic evaluation as well as potential solutions as an input for future research topics by the international Decision Support Initiative and other movements. Methods A survey on issues regarding the conduct, reporting and use of economic evaluation as well as on potential solutions was conducted using an online questionnaire among researchers who have experience in conducting economic evaluations in LMICs. The respondents were requested to consider the list of issues provided, rank the most important ones and propose solutions. A scoring system was applied to derive the ranking of difficulties according to researchers' responses. Issues were grouped into technical and context-specific difficulties and analysed separately as a whole and by region. Results Researchers considered the lack of quality local clinical data, poor reporting and insufficient data to conduct the analysis from the chosen perspective as the most important technical difficulties. On the other hand, the non-integration of economic evaluations into decision-making was considered the most important context-specific issue. Finally, context-specific issues were considered the larger barrier to the use of economic evaluation. Conclusion The technical issues that were considered most important were closely linked with the lack of an appropriately functioning information system as well as the capacity to generate essential contextual information (e.g. data and locally relevant utility values), especially when the methodology is complex. To overcome this, simpler approaches to collect data that yields information of comparable quality to more rigorous methods should be developed. The international community can play a major role through research on methodologies feasible for LMIC settings as well as in building research capacity in countries. Context-specific issues, which were recognised as larger barriers, should be improved in parallel.